LAMBDA ARCHITECTURE: UNIFYING BATCH AND REAL-TIME DATA PROCESSING AT SCALE - Seshendranath Balla Venkata (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Lambda Architecture represents a transformative approach to data processing that effectively bridges the gap between batch and real-time processing requirements in modern data systems. This comprehensive architecture addresses the fundamental challenges of data accuracy, system latency, and processing scalability through its innovative three-layer design. By combining batch processing capabilities with real-time streaming features, the architecture enables organizations to handle massive data volumes while maintaining high consistency and reliability. The framework demonstrates significant advantages in code reusability, fault tolerance, and system maintainability, making it particularly valuable for enterprises dealing with complex data processing needs. Through detailed article analysis of implementation components, technical challenges, and real-world applications, this article explores how Lambda Architecture has revolutionized data processing across various domains, from fraud detection to IoT applications. The architecture's ability to balance competing requirements of data accuracy and processing speed, while providing robust scalability and fault tolerance, has established it as a cornerstone solution in modern data processing systems.